103 | | $\alpha_0 = -\frac{2F_{ij}\delta_{ij}}{\Delta x^2}$ |
104 | | |
105 | | $\alpha_{\pm j} = \pm \frac{E_j }{2 \Delta x} + \frac{F_{jj}}{\Delta x^2}$ |
106 | | |
107 | | $\alpha_{\pm i, \pm j} = \pm \pm \frac{F_{ij}}{4 \Delta x^2}$ |
| 103 | $\alpha_0 = -\frac{B^{ij}_{\hat{i}} + B^{ij}_{-\hat{i}}}{\Delta x^2}\delta_{ij}$ |
| 104 | |
| 105 | $\alpha_{\pm j} = \frac{B^{jj}_{\pm \hat{j}}}{\Delta x^2}$ |
| 106 | |
| 107 | $\alpha_{\pm i, \pm j} = \pm \pm \frac{B^{ij}_{\pm \hat{i}}}{4 \Delta x^2} $ where the $\pm$ in $B_{\pm \hat{i}}$ corresponds to the $\pm i$ term. |